Smart Medicine Dispenser System - Om Kokane; Krushna Kamble; Ayush Kadam; Anushka Kamthe; Prajakta Deshmukh (International Journal of Scientific Research in Science and Technology, 2026)
This paper presents the design and implementation of an automated Smart Medicine Dispenser System using the ESP32 microcontroller integrated with IoT capabilities. The system addresses the critical challenge of medication non-adherence by automating the dispensing process and providing real-time reminders through multiple alert mechanisms. Hardware components including the DS3231 Real-Time Clock (RTC) module, 16x2 I2C LCD display, active buzzer, push button, and servo motor are interfaced with the ESP32 to enable scheduled dispensing, user acknowledgment, and remote monitoring. The system hosts an onboard web server that allows users to manage schedules and confirm medication intake through a browser-based interface. Experimental results demonstrate reliable timing, accurate dispensing, and seamless IoT integration, validating the proposed system as a low-cost and efficient solution for autonomous medication management in home and clinical environments.